Prophylactic Antibiotic Choice and Risk of Surgical Site Infection After Hysterectomy - Uppal, Shitanshu (Obstet Gynecol, 2016)
OBJECTIVE: To evaluate associations between prophylactic preoperative antibiotic choice and surgical site infection rates after hysterectomy. METHODS: A retrospective cohort study was performed of patients in the Michigan Surgical Quality Collaborative undergoing hysterectomy from July 2012 to February 2015. The primary outcome was a composite outcome of any surgical site infection (superficial surgical site infections or combined deep–organ space surgical site infections). Preoperative antibiotics were categorized based on the recommendations set forth by the American College of Obstetricians and Gynecologists and the Surgical Care Improvement Project. Patients receiving a recommended antibiotic regimen were categorized into those receiving beta-lactam antibiotics and those receiving alternatives to beta-lactam antibiotics. Patients receiving non-recommended antibiotics were categorized into those receiving overtreatment (excluded from further analysis) and those receiving non-standard antibiotics. Multivariable logistic regression models were developed to estimate the independent effect of antibiotic choice. Propensity score matching analysis was performed to validate the results. RESULTS: The study included 21,358 hysterectomies. The overall rate of any surgical site infection’ was 2.06% (N=441). Unadjusted rates of ‘any surgical site infection’ were 1.8%, 3.1% and 3.7% for beta-lactam, beta-lactam alternatives and non-standard groups, respectively. After adjusting for patient and operative factors within clusters of hospitals, compared to the beta-lactam antibiotics (reference group), the risk of ‘any surgical site infection’ was higher for the group receiving beta-lactam alternatives (OR 1.7, CI 1.27–2.07) or the non-standard antibiotics (OR 2.0, CI 1.31–3.1). CONCLUSION: Compared to women receiving beta lactam antibiotic regimens, there is a higher risk of surgical site infection after hysterectomy among those receiving a recommended beta lactam alternative or non-standard regimen.